(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study investigates the impact of role overload and role ambiguity on employee performance, emphasizing the role of compensation as an intervening variable. Conducted within the healthcare service sector at Telkomedika Central Java Region, the research addresses a pressing organizational issue: how unclear roles and excessive workloads can negatively influence workforce performance and satisfaction. Drawing on the theory of role stress, the study seeks to provide empirical evidence on the mechanisms through which stressors impair employee output, and how compensation may serve as a mitigating factor. A quantitative approach was employed, involving the entire population of 124 employees across the Semarang, Solo, and Yogyakarta branches. Data were collected through structured questionnaires and analyzed using multiple regression techniques. The results demonstrate that both role overload and role ambiguity significantly and negatively impact employee performance (p < 0.05). Additionally, compensation has a positive and statistically significant influence on performance, and it partially mediates the relationship between role stress and performance outcomes. These findings suggest that organizations should consider role clarity and workload balance as essential management priorities. Furthermore, designing fair and motivating compensation systems can buffer the adverse effects of workplace stressors, ultimately improving employee engagement and productivity. This study contributes to the literature by highlighting the mediating role of compensation in the stress-performance relationship, especially within high-pressure service industries in Indonesia.